Generalized hyperbolic functions to find soliton-like solutions for a system of coupled nonlinear Schrödinger equations - Yomba, Emmanuel (Physics letters. A, 2008)
With the aid of symbolic computation, we demonstrate that the known method which is based on the new generalized hyperbolic functions and the new kinds of generalized hyperbolic function transformations, generates classes of exact solutions to a system of coupled nonlinear Schrödinger equations. This system includes the modified Hubbard model and the system of coupled nonlinear Schrödinger derived by Lazarides and Tsironis. Four types of solutions for this system are given explicitly, namely: new bright–bright, new dark–dark, new bright–dark and new dark–bright solitons.